Heal rate of metatarsal fractures: A propensity-matching study of patients treated with low-intensity pulsed ultrasound (LIPUS) vs. surgical and other treatments. Issue 11 (November 2016) - Nolte, Peter; Anderson, Robert; Strauss, Elton; Wang, Zhe; Hu, Liuyi; Xu, Zekun; Steen, R. Grant
Abstract: Introduction: Whether to treat metatarsal fractures conservatively or surgically is controversial. We test a hypothesis that metatarsal fractures treated conservatively with non-invasive low-intensity pulsed ultrasound (LIPUS) obtain heal rates comparable to current surgical techniques. Patients and methods: This is a retrospective observational cohort study, using patient outcomes from a prospectively-collected LIPUS registry required by the U.S. Food & Drug Administration. Registry data were collected over a 5-year period and were reviewed and validated by a registered nurse. Data required for analysis were days-to-treatment (DTT) with LIPUS and a dichotomous outcome of healed versus failed, as assessed by clinical and radiographic criteria. Registry patients (DTT < 365 days) were propensity-matched to metatarsal fracture patients from a health claims database that includes medical and drug expenses for ∼90.1 million patients. The propensity match was based on patient demographic data (age, gender, body weight, fracture severity, and smoking status). Results: A total of 594 metatarsal fractures were treated with LIPUS, including 161 Jones fractures. Compared to patients in the claims database, LIPUS-treated patients were more likely to: be overweight or obese; be male; have open fracture; and smoke (all, P < 0.0001), suggesting that these variables were perceived as nonunion risk factors by prescribing physicians. After propensity-matching, none of these differences between the registry and the health claims database remained significant. The heal rate with LIPUS treatment was 97.3%, comparable to the heal rate of 95.3% among claims patients in 2011 who did not receive LIPUS (P = 0.0654). When fresh fractures (0–90 days) and delayed unions (91–365 days) were analyzed separately, the LIPUS fresh fracture heal rate was superior to claims patients (P = 0.0381), and the delayed union heal rate was comparable. After exclusion of registry patients who received surgery, heal rate with LIPUS alone (97.4%) was significantly better (P < 0.0097) than the heal rate for matched patients in 2011 (94.2%). Conclusions: LIPUS significantly improved the heal rate of metatarsal fractures <1 year old without surgery (P = 0.0097). Metatarsal fractures treated with LIPUS alone have a heal rate comparable to fractures treated by surgical intervention.